Strategy and decision making in karate - Frigout, J.; Tasseel-Ponche, S.; Delafontaine, A. (Frontiers in Psychology, 2020)
Karate will be included in the 2020 Summer Olympics in Tokyo as an additional sport. The inner logic of this activity includes a specific scoring system and way of modeling. Three hundred and nine bouts were observed in the competition context, which resulted in new perspectives on training and competition. The scoring of punches (43.7% of total scored points) and face kicks (37.9%) appears to be more significant (p = 0.01) than that of body kicks (15.3%, p = 0.01) and leg-sweeping (3.1%, p = 0.31). Penalties appear to be very significant and associated with victory when "scored" by the competitor against himself or herself (p = 0.01). Competitors must score points and penalties. This zero-sum game induces a simple rivalry, whose purpose is domination and which must rely on a predefined strategy and initiative. Karatekas have to make decisions, such as when taking the risk to score points and penalties, whether or not they lead the score. Karatekas may decide to expose or protect themselves, create situations, or simply remain realistic and adhere to the plan. The question of decision making, which is central to this work, forces us to focus our future work on the notions of expectations and self-fulfilling prophecies.